2021
DOI: 10.1002/ijc.33863
|View full text |Cite
|
Sign up to set email alerts
|

Effect and mechanism of circRNAs in tumor angiogenesis and clinical application

Abstract: Tumor blood vessels provide oxygen and necessary nutrients for the tumor, which provides the basis for tumor metastasis. Therefore, tumor angiogenesis plays a very important role in tumor growth and metastasis. In contrast to linear RNAs, circRNAs represent a type of closed‐loop RNA with diverse biological functions. At the same time, circRNAs have strong stability, timeliness, tissue specificity and disease specificity. With the rapid development of next‐generation sequencing and bioinformatics, there have be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 74 publications
0
11
0
Order By: Relevance
“…First, our study did not include enough clinical samples, and there was a lack of relevant follow-up prognostic information, which made it difficult for us to analyze the correlation between circPOLR2A expression and cRCC prognosis. Due to the stability of circRNAs endowed by their loop structure, several studies have demonstrated the clinical application potential of circRNAs as cancer biomarkers [77,[82][83][84]. Hence, including more cRCC samples with sufficient follow-up data is necessary for evaluating the clinical value of circPOLR2A in future research, which is of great significance for subsequent clinical transformation.…”
Section: Discussionmentioning
confidence: 99%
“…First, our study did not include enough clinical samples, and there was a lack of relevant follow-up prognostic information, which made it difficult for us to analyze the correlation between circPOLR2A expression and cRCC prognosis. Due to the stability of circRNAs endowed by their loop structure, several studies have demonstrated the clinical application potential of circRNAs as cancer biomarkers [77,[82][83][84]. Hence, including more cRCC samples with sufficient follow-up data is necessary for evaluating the clinical value of circPOLR2A in future research, which is of great significance for subsequent clinical transformation.…”
Section: Discussionmentioning
confidence: 99%
“… 17 CircRNAs are characterized as being stable, specific, and well conserved and have been suggested to be vital participants in carcinogenesis, making them possible candidates for cancer screening. 18 , 19 , 20 Accordingly, circRNAs have attracted more attention in tumor pathogenesis and biomarker research in recent years. In the field of GC, a number of abnormally expressed circRNAs have been discovered, and their functions and molecular mechanisms have been revealed.…”
Section: Discussionmentioning
confidence: 99%
“…The rapid development of biological technologies has contributed to the in‐depth exploration of functional circRNAs 17 . CircRNAs are characterized as being stable, specific, and well conserved and have been suggested to be vital participants in carcinogenesis, making them possible candidates for cancer screening 18‐20 . Accordingly, circRNAs have attracted more attention in tumor pathogenesis and biomarker research in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…A growing body of literature has long shown that mRNAs, miRNAs, lncRNAs, and circRNAs can be used as diagnostic and prognostic biomarkers for certain cancers [23,24,25,26,27,28]. Genetic signature-based risk models have also been widely reported to show high prognostic accuracy in many other cancer types [29,30,31,32].…”
Section: Discussionmentioning
confidence: 99%